Environmental literacy research trends in education: A systematic literature review - Rofiqi, Ainur (Department of Biology Education, Universitas Pendidikan Indonesia, 2024)
Environmental literacy is a key concept in promoting individual attitudes towards conscious lifestyle changes towards environmental challenges in a sustainable manner. This research is a systematic literature review by analyzing articles from 2018-April 2023 with environmental literacy in education as the main focus. This study aims to collect information related to various studies on environmental literacy in education in Indonesia. The results showed an increase in publication trends, the dominant research was quantitative research, besides that grade 7 and 10 students became the most subjects. Tests and percentage analysis are instruments and methods of data analysis used successively, and the most treatment is in the form of environmental literacy tests. The recommendations proposed for the next research are increasing the diversity of research types, research subjects, as well as the selection of appropriate instruments and data analysis.